Debates over orphan drug pricing: a meta-narrative literature review - Matthew S. Hanchard (Orphanet Journal of Rare Diseases)
Abstract Rare disease prevalence rates are increasing rapidly worldwide, as are the cost of orphan indication drugs used to treat them, posing significant strain on many healthcare systems. In response, a set of tensions have arisen within academic, activist, advocacy, industry, and policy circles over orphan drug pricing. Yet there has to date been no unifying review of the literature engaging critically with these tensions. Addressing this gap, the article examines the narratives in circulation around orphan pricing, the traditions and epistemic bases they draw on, and their points of contestation/coalescence. It does so through a meta-narrative literature review, finding three core narratives. One involves dispute over outlay costs for developing new orphan drugs, often drawing on normative health economics with a base in practical idealism. It argues that (bio)pharmaceutical manufacturers misuse policy incentives to profit excessively through monopoly capitalism. A second narrative draws on both empirical and normative health economics (often steeped in empiricism paired with a utilitarian standpoint). It contends that high orphan drug prices signify a healthy market and justifiably support longer-term innovation while promoting wider equity of access. A third (midway) narrative draws on the sociology of health and innovation studies alongside normative health economics and health policy studies to suggest alternative models of innovation and valuation. As a unifying meta-narrative, the review finds a sustained call for reform, centred on welfare economics and resource allocation, where current incentives and regulations are held to be insufficient. Overall, the article recommends that regulators look to alternative models of innovation steeped in social science thinking to modify reviewing appraisal, coverage, and reimbursement processes for orphan drugs. Also, that greater patient inclusion and transparency would help include a wider range of intangible social factors that rare disease patients face in accessing high priced orphan drugs.